Risk Perception Dynamics and Equity Share Investment Behaviour - Singh, Ranjit; Bhowal, Amalesh (Indian Journal of Finance, 2009)
Very often it came to the mind of the people that what are the factors which drives the investors’ behaviour. It is also seen that one believes that he/she is behaving rationally while at the same time assuming that others often do not. Most of the investment and financial theories are based on the idea that everyone takes careful account of all available information before making investment decisions. But there is much evidence that it is not the case. Behavioral finance, a study of the markets that draws on psychology, is throwing more light on why people buy or sell the stocks they do - and even why they do not buy stocks at all ( Singh R&Bhowal A, 2007). This research on investor behavior helps to explain the various ’market anomalies’ that challenge standard theory. It is emerging from the academic world and beginning to be used in money management.